Necrotizing Enteritis and Hyperammonemic Encephalopathy Associated With Equine Coronavirus Infection in Equids. (November 2015) - Giannitti, F.; Diab, S.; Mete, A.; Stanton, J. B.; Fielding, L.; Crossley, B.; Sverlow, K.; Fish, S.; Mapes, S.; Scott, L.; Pusterla, N.
Equine coronavirus (ECoV) is a Betacoronavirus recently associated clinically and epidemiologically with emerging outbreaks of pyrogenic, enteric, and/or neurologic disease in horses in the United States, Japan, and Europe. We describe the pathologic, immunohistochemical, ultrastructural, and molecular findings in 2 horses and 1 donkey that succumbed to natural infection with ECoV. One horse and the donkey (case Nos. 1, 3) had severe diffuse necrotizing enteritis with marked villous attenuation, epithelial cell necrosis at the tips of the villi, neutrophilic and fibrinous extravasation into the small intestinal lumen (pseudomembrane formation), as well as crypt necrosis, microthrombosis, and hemorrhage. The other horse (case No. 2) had hyperammonemic encephalopathy with Alzheimer type II astrocytosis throughout the cerebral cortex. ECoV was detected by quantitative polymerase chain reaction in small intestinal tissue, contents, and/or feces, and coronavirus antigen was detected by immunohistochemistry in the small intestine in all cases. Coronavirus-like particles characterized by spherical, moderately electron lucent, enveloped virions with distinct peplomer-like structures projecting from the surface were detected by negatively stained transmission electron microscopy in small intestine in case No. 1, and transmission electron microscopy of fixed small intestinal tissue from the same case revealed similar 85- to 100-nm intracytoplasmic particles located in vacuoles and free in the cytoplasm of unidentified (presumably epithelial) cells. Sequence comparison showed 97.9% to 99.0% sequence identity with the ECoV-NC99 and Tokachi09 strains. All together, these results indicate that ECoV is associated with necrotizing enteritis and hyperammonemic encephalopathy in equids.